2010
DOI: 10.1017/s1478951509990708
|View full text |Cite
|
Sign up to set email alerts
|

Multiple evaluation of a hospital-based palliative care consultation team in a university hospital: Activities, patient outcome, and referring staff's view

Abstract: This study showed that the PCCT performed comprehensive assessments on referred patients and provided extra support. No patient's QOL 1 week after referral was improved with the exception of insomnia. Referring staff highly evaluated the activities of the PCCT. In the evaluation of PCCTs, further research about the variation of clinical activities of PCCTs, their applicability, and benefit is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Specialist palliative care team membership varied considerably ( (31,42) and Neurology (39,45) professionals found these providers preferred and took a more linear approach to palliative care involvement. Of the seven remaining studies, three did not provide enough information to determine model of care (30,33,52), three reported that integrated care is desired but not actualised into patient care (37,41,46), and one reported a mixed response about which model of care was preferred (40).…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialist palliative care team membership varied considerably ( (31,42) and Neurology (39,45) professionals found these providers preferred and took a more linear approach to palliative care involvement. Of the seven remaining studies, three did not provide enough information to determine model of care (30,33,52), three reported that integrated care is desired but not actualised into patient care (37,41,46), and one reported a mixed response about which model of care was preferred (40).…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Areas where generalist teams were able to acknowledge their own discomfort and lack of expertise mirrored the areas for which they were more likely to integrate specialist palliative care services unrelated to country, disease type, hospital size, or specialist palliative care team membership. Trust and utilisation were fostered when both the referring team and the specialist palliative care team were able to express mutual respect and appreciation for each other's roles, expertise, and contributions to patient care outcomes, and when communication was high(35,36, 38,48,49,51,52).The attention to skill-building vs. deskilling was shared by all provider types (nurse, physician, social worker, administrators, etc. ), persisted regardless of specialist palliative care team membership, country, or hospital size.…”
mentioning
confidence: 99%
“…The demand for specialist PC in hospitals cannot be covered by PC units only [9,10], and it concerns a large variety of chronic diseasesnot only cancer [6,11,12]. Inpatient palliative care consultation (IPCC) teams have been established and shown a lowering of symptom burden in patients and their family caregivers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The patients’ perception of their general well-being and satisfaction with their care experience had also improved [12, 14]. Although most studies suggest that patients benefit from PC, there are studies reporting no differences/improvements in symptom scores [14, 15]. In addition, PCCTs are reported to be up-to-date “do not resuscitate/do not intubate” orders and up-to-date comfort care orders, and that patients were referred for hospice care [10, 16], but less admitted to, or to die in intensive care units [14, 1719].…”
Section: Introductionmentioning
confidence: 99%
“…The available studies report that PCCTs are expected by primary healthcare team members to be experts in managing difficult symptoms and complex psychosocial problems, in communication and emotional support and to clarify care goals [3, 8, 11, 14]. In one survey, more than 90 % of the primary team member respondents considered the effect of the PCCT as excellent or good and were satisfied with the support provided [15]. Primary healthcare team members concluded that PCCT should be visible in the wards, be responsive and be easily accessible [24].…”
Section: Introductionmentioning
confidence: 99%